Cognitive science and artificial intelligence: simulating the human mind and its complexity. Issue 4 (27th November 2019) - Naveed Uddin, Mohd
Abstract : This study encompassed around the interdisciplinary study of cognitive science in the field of artificial intelligence. Past as well as current areas of research have been highlighted such that better understating of the topic can be ensured. Furthermore, some of the present‐day applications of cognitive science artificial intelligence have been discussed as these can be considered as the foundation for further improvement. Prior to discussion about future scopes, real‐time complexities have been revealed.